Central Diabetes Insipidus as a Post-Traumatic Endocrine Complication: a Case Report and Clinical Review - Pusvitasari, Luh Wira; Padma Amrita, Gede (Journal of Comprehensive Science, 2025)
Diabetes Insipidus is a rare disorder characterized by impaired water regulation due to insufficient secretion of antidiuretic hormone (central diabetes insipidus) or renal unresponsiveness to this hormone (nephrogenic diabetes insipidus). We present a case of Central Diabetes Insipidus (CDI) in an 18-year-old male following a traumatic brain injury (TBI) sustained in a motor vehicle accident. The patient was admitted to the intensive care unit with a diagnosis of epidural hemorrhage, intracerebral hemorrhage, brain compression, cerebral edema, and skull fracture. CDI was diagnosed on the second postoperative day based on polyuria (2.01 ml/kg/hour) and hypernatremia (170 mmol/L). Desmopressin therapy was initiated at a dose of 0.1 mg every 8 hours, leading to clinical improvement within 24 hours, with a reduction in diuresis (0.9 ml/kg/hour) and a decrease in serum sodium levels (160 mmol/L). Fluid therapy was administered using a combination of 5% Dextrose and 0.225% Sodium Chloride (4000 ml/24 hours) and 1200 ml of enteral water via nasogastric tube, based on calculated fluid requirements. CDI occurs when vasopressin neurons in the hypothalamus lose function, resulting in decreased production and/or impaired release of antidiuretic hormone. Desmopressin administration is effective in treating CDI, demonstrating a favorable therapeutic response.